2020
DOI: 10.1002/nvsm.1681
|View full text |Cite
|
Sign up to set email alerts
|

The influence of external reference price strategies in a nonprofit arts organization's “pay‐what‐you‐want” setting

Abstract: Nonprofit arts organizations face conflicting objectives to balance—or more specifically, to create—artistic and educational value and to generate financial income from various sources. Pay‐what‐you‐want (PWYW), a participative pricing mechanism where services have no fixed price and customers actively decide what to pay, is a novel pricing mechanism and is of high interest for organizations and researchers alike. Based on the concepts of loss aversion and gain, this study presents a field experiment to test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…In future, scholars should inspect other factors that could influence ERP at the seller and store level, like satisfaction, price consciousness and product involvement (Gerpott, 2017; Weisstein et al. , 2019; Gross et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In future, scholars should inspect other factors that could influence ERP at the seller and store level, like satisfaction, price consciousness and product involvement (Gerpott, 2017; Weisstein et al. , 2019; Gross et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…, 2009; Soule and Madrigal, 2015; Viglia et al. , 2019; Gross et al , 2020; Borg et al. , 2020; Lee et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Our studies showed that ERPs increase the amount consumers intend to pay, but they still offer considerably less than the ERP amount (NYOP = US$83.44, PWYW = US$55.40, ERP = US$116.00). Consumer behavior depends on other factors such as type of business or product and ERP presentation type (Gross et al, 2021), which may explain inconsistent results found for ERP on previous studies (e.g., Roy et al, 2021; Weisstein et al, 2016). Thus, our results should be carefully interpreted.…”
Section: General Discussion and Conclusionmentioning
confidence: 98%
“…Researchers often examine separate outcomes for NYOP and PWYW participative pricing mechanisms (e.g., Fay & Zeithammer, 2017; Gross et al, 2021; Narwal & Nayak, 2019; Roy et al, 2021), rather than comparing outcomes such as pricing satisfaction, pain of payment, and amount consumers intend to pay (Wagner & Pacheco, 2020). To address the gap, our main objective is to investigate the effects of both PWYW and NYOP on pricing satisfaction, pain of payment, and amount consumers intend to pay.…”
Section: Introductionmentioning
confidence: 99%
“…Which pricing strategies appeal most to consumers? For instance, experiments can be conducted to discover the effects of a novel pricing mechanism, Pay-what-you-want (i.e., a participative pricing mechanism where customers actively decide what to pay) (Gross et al, 2021) on purchases of Slow Food products.…”
Section: Final Considerationsmentioning
confidence: 99%